Student Satisfaction in Physical Education with Sports Facilities at SMA Negeri 12 Pekanbaru - Adriani , Tri Hesti; Apriani, Leni (Indonesian Journal of Sport Management, 2025)
Physical education is essential for students' physical and social development, and the availability of sports facilities in schools affects the quality of learning. However, research on student satisfaction with these facilities is still limited, creating a gap that needs to be addressed to understand their impact on the learning experience. This highlights the need for adequate facilities to enhance students' learning experiences. This study aims to assess student satisfaction with sports facilities at SMA Negeri 12 Pekanbaru. This study uses quantitative methods and descriptive statistical analysis, data were collected using a questionnaire with a Likert scale. This study with a total of 40 students. The conclusion in this study as a whole The survey of student satisfaction levels with the facilities and infrastructure of SMA Negeri 12 Pekanbaru obtained a frequency of 17 with 42.5% in the category Quite satisfied.